Study of the effectiveness of ventriculosubarachnoid drainage in neonatal hydrocephalus according to the data of the Republic of Crimea for the period 2000–2018 - O. V. Volkodav; S. A. Zinchenko; V. A. Khachatryan (Бюллетень сибирской медицины)
Despite the achieved success in the treatment of neonatal hydrocephalus, the task of restoring circulation, outflow, and absorption of cerebrospinal fluid (CSF) remains urgent.The aim of the study was to investigate the effectiveness of ventriculosubarachnoid drainage in compensating hydrocephalus without shunt implantation.Materials and methods. We collected and studied clinical material for the period from 2000 to 2018 according to the data of the Republic of Crimea. We identified groups of premature (n = 184) and full-term (n = 107) infants who underwent standard treatment with lumbar puncture, subgaleal drainage, and ventriculoperitoneal shunting (VPS). In case of ventricular occlusion in 143 premature and 46 full-term infants, at the initial stage of treatment, the option of coronary – lambdoid subarachnoid ventriculostomy (RF Patent No. 2715535) in combination with lumbar punctures was included. With progression of hydrocephalus, ventriculosubarachnoid stenting (RF Patent No. 2721455) with subgaleal drainage was considered as an option.Results. The inclusion of the proposed options made it possible to increase the rate of hydrocephalus compensation without VPS to 75.5% in premature infants and to 80.4% in full-term infants versus 28.3% and 20.6%, respectively, according to the standard protocol (p < 0.001). In other cases, the imbalance between CSF production and absorption persisted, which required integration of a stent with a peritoneal part of the shunt, without replacing the system.Conclusion. The obtained result allows to consider the inclusion of the proposed options in the modern treatment algorithm for neonatal hydrocephalus.